The Value of Health Insurance: A Household Job Search Approach - Ginja, Rita; Conti, Gabriella; Narita, Renata (Journal of Labor Economics, 2025)
Does access to free health insurance affect household labor supply decisions? We address this question by exploiting the 2002 introduction of universal health insurance in Mexico (Seguro Popular, SP) that broke the link between access to health care and job contract. Reducedform estimates show that SP increased informality among less educated families with children by 3.5%. We develop and estimate a household search model that incorporates the value of formal sector amenities relative to pre-reform alternatives, and the value of health insurance. Model estimates show that households value SP by, at most, 1.33 per unit of net cost.